KAJIAN PERTUMBUHAN TANAMAN PISANG BERANGA KELIMUTU - Eko H. Juwaningsih (Partner, 2008)
Study on Growth of Beranga Kelimutu Banana. This research aimed to collect data on ecological characteristic of banana cultivated in some regions in NTT, performance, and agronomic practice of the banana. Data collected were primary data and secondary data. Primary data consisted of soil properties (moisture, pH, porosity, structure and consistency; NPK content, nutrient content of fruit (glucose, protein, lipid, crude fiber, vitamin C, and Kalium). The entire data were examined using appropriate method. Genetic characteristics of beranga Kelimutu were measured using SDS PAGE. The result showed that the performance of beranga varied among regions due to the difference of soil condition. Some regions are very suitable for growing of beranga. Plant cultivation, such as irrigation, weeding, pruning, fertilizing, and controlling of pests, could increase quantity and quality of yield, although their environment are suitable for development of plant.Based on profile, there was similarity of band from Ndito and Baumata variety. In addition, there was similarity or not similarity specific band at beranga from Nelle Orang, Benpasi, Lokoboko, Bloro, and Kefa Selatan. The existence of band 11 (40,5 kDa), 12 (36 kDa), 14 (33 kDa), 17 (26 kDa) and 18 (25,5 kDa) or not existency of these bands was specific band that differs beranga from Ndito and other varieties that grow outside. Based on plant performance of research location, Lokoboko, Temu and Baumata are suitable for nursery.Key word: banana performance, ecological characteristics of beranga